Kepatuhan Mengikuti Prolanis BPJS dengan Hasil Pemeriksaan HbA1c pada Penderita Diabetes Melitus - Festy Ladyani; Rita Agustina; Hernowo Anggoro Wasono; Hifta Faradilla (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Indonesia ranks 7th with the most diabetes mellitus in the world. BPJS Health as the organizer of the social security program applies the Chronic Disease Management Program (Prolanis) accompanied by a special HbA1c examination for diabetics. The results of the HbA1c examination can be influenced by various factors, one of which is in compliance with Prolanis. Research Objectives: To find out the relationship between compliance with BPJS PROLANISTS and HbA1c examination results in patients with diabetes mellitus in health centers. Research Methods: This research is a quantitative analytic study with a cross-sectional design. The sampling technique in the form of total sampling. The sample of this study was Prolanis participants with diabetes mellitus at the Kedaton Health Center. The instrument of this research was the medical record of Prolanis participants and the attendance of Prolanis. Research Results: Chi-square statistical test results with fisher exact alternative test found no relationship with the results of p = 1,000 (p> 0.05). Conclusion: There is no relationship between adherence to following Prolanis with the results of the HbA1c examination.